Bioaugmentation of sequencing batch reactor for aniline treatment during start-up period: Investigation of microbial community structure of activated sludge. (March 2020) - Li, Yao; Zhang, Qian; Li, Meng; Sang, Wenjiao; Wang, Ying; Wu, Lanfeng; Yang, Yiqin
Abstract: The rapid start-up of sequencing batch reactor (SBR) was studied by adding efficient aniline-degrading bacteria strain AD4 ( Delftia sp . ), and the reactor start-up completion took only 15 days. The loading rate of aniline was 0.7 g aniline (g VSS*d)-1, which has been completely removed. The NH4+-N produced in the degradation process of aniline was also converted, which made the concentration of NH4+-N in the effluent of the reactor was always lower than that in the influent. Nitrification and denitrification played some roles in forming a dynamic equilibrium state of the whole system. The variation of microbial community during the start-up of the reactor was analyzed by high-throughput sequencing. At the phylum level, Proteobacteria, Bacteroidetes and Actinobacteria have always accounted for a large proportion. They also serve as functional bacteria for both aniline degradation and nitrogen removal. The biggest percentage jump was Flavobacterium and Acidovorax . The amount of high efficiency aniline degradation bacterium AD4 in the reactor increased at first, followed by decreasing and finally stabilized, which played an important role in the degradation of aniline. Highlights: The rapid start-up of the SBR reactor was successfully completed in 15 days by bioaugmentation. High removal efficiency of aniline and ideal nitrogen removal effect were achieved in the reactor. Proteobacteria, Bacteroidetes and Actinobacteria always accounts for a large proportion. Flavobacterium 、 Acidovorax and Pseudomonas is the main functional groups in denitrification.